Synergy of grain boundary and interface diffusion during intermediate compound formation. Issue 8 (18th April 2023) - Gusak, Andriy; Titova, Anastasiia
ABSTRACT: The kinetics of reactive growth of a compound with a columnar structure with frozen bulk diffusion is revisited. The finite rate of redistribution and reaction along moving interfaces between reagents and growing compound is taken into account. Cases of planar and curved inter-phase interfaces are discussed. A new kinetic equation for the phase growth with evolving grain boundaries is suggested. Three cases are considered: (1) frozen grain structure, (2) normal lateral grain growth which does not depend on phase growth and on diffusion fluxes, (3) flux-driven grain growth which is induced by grain-boundary diffusion fluxes across the growing compound layer. The latter model provides the best fit to the experimental data.